1989
DOI: 10.1111/j.1440-1827.1989.tb02440.x
|View full text |Cite
|
Sign up to set email alerts
|

Squamous Differentiation in Thyroid Carcinoma With Special Reference to Histogenesis of Squamous Cell Carcinoma of the Thyroid

Abstract: Squamous differentiation of thyroid carcinoma was studied clinicopathologically and immunohistochemically i n 29 autopsy cases. Tumor cell nests with squamous differentiation (CNSD), which histologically resembled squamous cell carcinoma, were found i n 6 cases (20.7%). All of these 6 cases with CNSD had areas of undifferentiated carcinoma, representing 31.6% of 19 cases with undifferentiated carcinoma, and all but one case also showed coexisting papillary carcinoma. The CNSD were histologically associated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

1994
1994
2010
2010

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…We observed that both squamous differentiation and mucin‐producing cells were observed in two cases of ITET/CASTLE. Squamous differentiation has been described in papillary carcinoma, SCC, MEC, and AC 14–18. Mucin‐producing cells may be seen in papillary carcinoma, FC, MC, MEC, and metastatic adenocarcinoma 19–23.…”
Section: Discussionmentioning
confidence: 99%
“…We observed that both squamous differentiation and mucin‐producing cells were observed in two cases of ITET/CASTLE. Squamous differentiation has been described in papillary carcinoma, SCC, MEC, and AC 14–18. Mucin‐producing cells may be seen in papillary carcinoma, FC, MC, MEC, and metastatic adenocarcinoma 19–23.…”
Section: Discussionmentioning
confidence: 99%
“…Squamous differentiation of papillary and anaplastic thyroid carcinomas was also observed in routine histological studies. 34,35 Interestingly, it has been suggested earlier that the expression of type VII collagen in carcinomas would correlate more with the presence of squamous differentiation than the histogenetic origin of the tumour. 18 In agreement with our results, while this manuscript was under review, the expression of typical stratified epithelial cks 5/6 and 13 in papillary thyroid carcinomas was reported.…”
Section: Discussionmentioning
confidence: 99%
“…15 This definition of SCC is quite important, since up to 43% of papillary carcinomas will contain regions of squamous-cell metaplasia, and many anaplastic carcinomas will be comprised, in part, of squamoid regions. 9,16 Using these strict criteria, the incidence of SCC of the thyroid is less than 1% of all thyroid malignancies. 17,18 The origin of primary SCC within the thyroid remains controversial, and several hypotheses have been proposed.…”
Section: Scc Of Epithelial Cell Originmentioning
confidence: 99%